The Structure of the Complex between Yeast Frataxin and Ferrochelatase: CHARACTERIZATION AND PRE-STEADY STATE REACTION OF FERROUS IRON DELIVERY AND HEME SYNTHESIS - Söderberg, Christopher (J Biol Chem, 2016)
Frataxin is a mitochondrial iron-binding protein involved in iron storage, detoxification, and delivery for iron sulfur-cluster assembly and heme biosynthesis. The ability of frataxin from different organisms to populate multiple oligomeric states in the presence of metal ions, e.g. Fe(2+) and Co(2+), led to the suggestion that different oligomers contribute to the functions of frataxin. Here we report on the complex between yeast frataxin and ferrochelatase, the terminal enzyme of heme biosynthesis. Protein-protein docking and cross-linking in combination with mass spectroscopic analysis and single-particle reconstruction from negatively stained electron microscopic images were used to verify the Yfh1-ferrochelatase interactions. The model of the complex indicates that at the 2:1 Fe(2+)-to-protein ratio, when Yfh1 populates a trimeric state, there are two interaction interfaces between frataxin and the ferrochelatase dimer. Each interaction site involves one ferrochelatase monomer and one frataxin trimer, with conserved polar and charged amino acids of the two proteins positioned at hydrogen-bonding distances from each other. One of the subunits of the Yfh1 trimer interacts extensively with one subunit of the ferrochelatase dimer, contributing to the stability of the complex, whereas another trimer subunit is positioned for Fe(2+) delivery. Single-turnover stopped-flow kinetics experiments demonstrate that increased rates of heme production result from monomers, dimers, and trimers, indicating that these forms are most efficient in delivering Fe(2+) to ferrochelatase and sustaining porphyrin metalation. Furthermore, they support the proposal that frataxin-mediated delivery of this potentially toxic substrate overcomes formation of reactive oxygen species.